A Cross-Sectional Analysis to Assess Knowledge, Perception and Determinants of Self-Medication Practices - H, Hiba; M, Malathi; M, Mariyam; Bhattacharjee, Anubhab; Puranik, Dayanand (Indian Journal of Pharmacy Practice)
Background: As per WHO, Self-medication involves selecting medicines for self-diagnosed conditions, often without medical consultation, leading to misuse. Limited research examines how knowledge, attitude and practices influence misuse. Thus, this study aimed to assess the prevalence of SMP and to evaluate knowledge, perception, practices and determinants of SMP among participants. Materials and Methods: This prospective cross-sectional study was carried out using a validated self-administered questionnaire from staff and students during the 2022-23 academic years. Results: The overall prevalence of SMP was high at 72.6%. Females had a higher rate of SM (83.3%), with the 26-30 age groups being the most prevalent. Among healthcare students, Ph.D. students had the highest SMP prevalence, while D. Pharma students had the lowest. Fourth-year students self-medicated more than others. The prevalence of SMP was notably higher among individuals with good knowledge compared to those with poor knowledge. Discipline and year of study were key predictors of good knowledge. Reasons for SMP included treating minor ailments and having medication knowledge. Commonly treated conditions were headaches, cough and cold. Medicines majorly used included antipyretics and antimicrobials. Most medicines were obtained from pharmacies and dosage information from PILs. Discontinuation of self-medication was mainly due to running out of medicines and symptom disappearance. Conclusion: The frequent self-medication with antimicrobials highlights the need for antibiotic stewardship programs. High self-medication rates call for advocacy and safe SMP training. Reducing SMP requires raising awareness of its risks and regulating pharmacies to dispense medicines rationally.
Keywords: Self-medication; Knowledge; Perception; Prevalence